Developing android-based literature theory learning media using the MIT App inventor application - Kurniawan, Rio; Hamzah, Syukri; Hiasa, Fina (JOALL (Journal of Applied Linguistics and Literature), 2024)
This study aims to develop an Android-based literary theory learning media using the inventor application in the independent learning era - independent campus. This study used the Research and Development (R & D) that refers to the model of the research and development of 4D (four-D), which is definition, design, development, and dissemination. The Android-based learning media developed was tested on students in the odd semester taking the course of Theory of Literature at the Department of Indonesian Education, Faculty of Teacher Training and Education, University of Bengkulu. Based on the results obtained from the questionnaires that were distributed in this study, which were from the results of material validation, data related to the learning media used in this study were declared suitable for use without revision. In terms of media appearance and display (text on the media, color combination on the media, images on the media, navigation board layout), the result in general was "strongly agree". In terms of usage (instructions for use and user interface), the result in general was "agree". Based on the results of questionnaire distribution to thirty students, the following results were obtained. Twenty-three students stated "strongly agree" and seven students stated "agree" to the learning indicators. Regarding the material indicator, twelve students stated "agree", eighteen students stated "strongly agree". Meanwhile, regarding the learning media display indicator, all students stated that they strongly agreed. With the usage indicators, twenty-one students agreed and nine students strongly agreed. The test in the form of giving questions to students aimed to discover the extent to which students understood the material after the Android-based learning media created using the MIT App Inventor application was tested. The data obtained revealed that 39% of students got an A, 51% of students got a B and 10% of students got a C.